Peppermint Oil Administration Can Stabilizes Blood Glucose and Improves Survival of Bonylip Barb in Closed Transportation System - Azizah, Latifah Nur Reza; Harwanto, Dicky; Suryaningtyas, Indyaswan Tegar; Nurhayati, Dewi (Departemen Akuakultur FPIK UNDIP, 2025)
Transportation of Bonylip barb fish is important for supports the production of cultivation and economic markets distribution. The high mortality of Bonylip barb seeds is an problem for Bonylip barb fish farmers. An addition of peppermint oil (Mentha piperita L.) attempts to suppress respiratory response and minimize mortality. The purposes the research was to test the effect of peppermint oil on Bonylip barb seeds and find out the best dosage of peppermint oil on Bonylip barb seeds. The research design is Completely Randomized Design consisting of 4 treatments and 3 replications, i.e. A (0 mL/L); B (0.1 mL/L); C (0.2 mL/L); and D (0.3 mL/L). This study used Bonylip barb seeds (3.33 ± 0.58 g) with density of 20 fish/L. Research procedures included seed preparation and acclimatization, fasting, adding peppermint oil, packaging, fish transportation for 8 hours, and rearing for 7 days. The results showed that peppermint oil had a significant effect on induction time, recovery time, blood glucose after transportation and maintenance, and survival life of Bonylip barb seeds. The best dose of peppermint oil was shown by 0.1 mL/L, which produced an induction time of 8.14 ± 5.07 minutes and a sedative time of 11.54 ± 2.60 minutes; fish blood glucose after transportation and maintenance was 68.33 ± 3.06 mg/dL and 64.67 ± 0.58 mg/dL, and the survival rate of 88.33 ± 5.77%. Result of this research is expected to provide essential guidance for fish farmers during the transportation of Bonylip barb, helping to enhance the safety and well-being of the fish throughout the shipping process